VO#49 Price quotation for BK1 works (architectural brick wall) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submitted quotation for architectural brick wall of BRACU new campus project.